Good jobs, bad jobs, and the Great Recession: Lessons from Japan's Lost Decade - Ryo Kambayashi; Takao Kato (Institute for the Study of Labor (IZA), 2012)
This paper provides novel evidence on the long-term effect of the Great Recession on the quality of jobs, in particular whether the Great Recession results in the replacement of good jobs (characterized by high wage/benefit, job security, and opportunity for training and development) with bad jobs (characterized by the lack of such attributes). Unfortunately there is not yet sufficiently long data from the recent Great Recession that enable researchers to study fully its long-term consequences for the labor market structure. To this end, we examine Japan's Lost Decade, the original Great Recession that occurred two decades ago. First, insofar as male workers are concerned, we find evidence against the popular narrative that during Japan's Lost Decade there was a significant shift of the composition of employment toward bad jobs. Second, we find that the composition of female workers shifted significantly toward bad jobs and that such a shift occurred primarily through an increased use of a hybrid employment contract of nonstandard employment with indefinite contracts. Third, young women in Japan made considerable progress in shifting the composition of their employment toward good jobs during Japan's growth decade preceding the Lost Decade. We find that such progress was entirely undone during the Great Recession. Obviously the Great Recession affects the quantity of jobs and policy makers ought to pay immediate attention to such quantity effects. However, the Great Recession may also have more long-term structural effects on the quality of jobs.
Keywords: J63; J64; J41; 330; job quality; good jobs; bad jobs; Great Recession; Lost Decade; Japan; Wirtschaftskrise; Arbeitsverhältnis; Ungeschützte Beschäftigung; Japan